Anthropogenic Carbon in the Arctic Ocean: Perspectives From Different Transient Tracers - Raimondi, Lorenza; id_orcid:0 000-0001-9107-7254; Wefing, Anne-Marie; id_orcid:0 000-0001-6855-6062; Casacuberta, Núria; id_orcid:0 000-0001-7316-1655 (Wiley, 2024)
In this study we investigated the physical characteristics of the Atlantic layer in the Arctic Ocean (AO) and its role in the distribution and storage of anthropogenic carbon (Cant). The novelty of this work is to use the Transit Time Distribution method (TTD) with the radionuclides 129I and 236U and its comparison to the commonly applied gas tracers, CFC-12 and SF6. Overall, our examination of two distinct tracer pairs, along with the novel TTD method in comparison to a classical approach, revealed a notable agreement, highlighting the robustness of these Cant estimates. The TTD analysis based on radionuclides showed that whereas the Eurasian Basin has shorter transit times and is dominated by strong mixing conditions, the Amerasian Basin is characterized by longer transit times and a strong advective flow. Overall, the Cant concentrations obtained from radionuclides confirm that the distribution in the AO follows its circulation patterns, with higher concentrations in the Eurasian Basin (∼50 μmol kg−1) compared to the Amerasian one (∼36–42 μmol kg−1). An estimated partial inventory of 0.85 ± 0.17 and 1.0 ± 0.03 Pg C was assessed for 2015 from the novel application of TTD with radionuclides and gas tracers, respectively. Finally, we identified the saturation of gas tracers as a larger source of uncertainty for Cant estimation compared to the uncertainty associated to different radionuclides' input functions, thus remarking the importance of including non-saturation dependent tracers, such as radionuclides, as an additional tool to support Cant estimates in the AO. ISSN:0148-0227 ISSN:2169-9275